2018
DOI: 10.4018/ijcrmm.2018070102
|View full text |Cite
|
Sign up to set email alerts
|

A Proposal Model for Measuring the Impact of Viral Marketing Through Social Networks on Purchasing Decision

Abstract: Viral marketing has become a conduit for today's organizations and an important pillar for managing the organization and a source that enhances its competitiveness and creates new opportunities for organizations through which they are trying to achieve competitive advantages to obtain new market shares. So, this study provides insight into how social network influence on purchasing decision through viral marketing and knowledge sharing on social networking sites (SNSs). By using the sample from 650 Egyptian co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 1 publication
1
3
0
Order By: Relevance
“…This means that the higher the viral marketing, the higher the purchase decision tends to be. Thus this study supports previous research by Ahmed (2018) that viral marketing has a positive and significant effect on purchase decisions. research is also in line with this study, namely Sembiring & Ananda (2019) that viral marketing plays a major role in shaping consumer purchasing decisions.…”
Section: Discussionsupporting
confidence: 92%
“…This means that the higher the viral marketing, the higher the purchase decision tends to be. Thus this study supports previous research by Ahmed (2018) that viral marketing has a positive and significant effect on purchase decisions. research is also in line with this study, namely Sembiring & Ananda (2019) that viral marketing plays a major role in shaping consumer purchasing decisions.…”
Section: Discussionsupporting
confidence: 92%
“…According to Ahmed (2018), his research on 650 individuals indicated that families and friends and viral marketing hugely affect the purchasing decision of consumers. Thus, purchasing decisions are mainly influenced by the spread of word-of-mouth, comments, and effective viral marketing strategies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…where n is the number of concepts and f (•) denotes the transfer function to squeeze the result of the multiplication into a specific range, e.g., [0,1] [29] to consider the previous value of each concept, i.e., observing the self-loop effect. Hence, Equation (16) can be modified and extended as follows:…”
Section: Fuzzy Cognitive Mapmentioning
confidence: 99%
“…Key person identification within a social network means to find persons who can change the feelings, attitudes, or behaviors of other persons though network relationships [1] and, therefore, this is a critical issue in the fields of viral marketing [2], spread of opinions [3], rumor restraint [3], and innovation dissemination [4]. As we know, one of the major properties within social networks is its symmetry between nodes.…”
Section: Introductionmentioning
confidence: 99%